Metformin exerted tumoricidal effects on colon cancer tumoroids via the regulation of autophagy pathway - Roya Shabkhizan; Çığır Biray Avci; Sanya Haiaty; Marziyeh Sadat Moslehian; Fatemeh Sadeghsoltani; Ahad Bazmani; Mahdi Mahdipour; Leila Sabour Takanlou; Maryam Sabour Takanlou; Arezoo Rezaie Nezhad Zamani; Reza Rahbarghazi (Stem Cell Research & Therapy)
Abstract Background Despite the existence of promising outcomes from standard 2D culture systems, these data are not completely akin to in vivo tumor parenchyma. Therefore, the development and fabrication of various 3D culture systems can in part mimic intricate cell-to-cell interaction within the real tumor mass. Here, we aimed to evaluate the tumoricidal impacts of metformin (MTF) on colorectal cancer (CRC) tumoroids in an in vitro system via the modulation of autophagy. Methods CRC tumoroids were developed using human umbilical vein endothelial cells (HUVECs), adenocarcinoma HT29 cells, and fibroblasts (HFFF2) in a ratio of 1: 2: 1 and 2.5% methylcellulose. Tumoroids were exposed to different concentrations of MTF, ranging from 20 to 1000 mM, for 72 h. The survival rate was detected using an LDH release assay. The expression and protein levels of autophagy-related factors were measured using PCR array and western blotting, respectively. Using H & E, and immunofluorescence staining (Ki-67), the integrity and proliferation rate of CRC tumoroids were examined. Results The current protocol yielded typical compact tumoroids with a dark central region. Despite slight changes in released LDH contents, no statistically significant differences were achieved in terms of cell toxicity in MTF-exposed groups compared to the control tumoroids, indicating the insufficiency of MTF in the induction of tumor cell death (p > 0.05). Western blotting indicated that the LC3II/I ratio was reduced in tumoroids exposed to 120 mM MTF (p < 0.05). These data coincided with the reduction of intracellular p62 content in MTF 120 mM-treated tumoroids compared to MTF 40 mM and control groups (p < 0.05). PCR array analysis confirmed the up-regulation, and down-regulation of several genes related to various signaling transduction pathways associated with autophagy machinery and shared effectors between autophagy and apoptosis in 40 and 120 mM MTF groups compared to the non-treated control group (p < 0.05). These changes were more prominent in tumoroids incubated with 120 mM MTF. Histological examination confirmed the loosening integrity of tumoroids in MTF-treated groups, especially 120 mM MTF, with the increase in cell death via the induction of apoptosis (chromatin marginalization) and necrotic (pyknotic nuclei) changes. In the 120 mM MTF group, spindle-shaped cells with the remnants of a fibrillar matrix were detected. Data indicated the reduction of proliferating Ki-67+ cells within the tumoroids by increasing the MTF concentration from 40 to 120 mM. Conclusions Different shared autophagy/apoptosis genes were modulated in CRC tumoroids after MTF treatment coinciding with both typical necrotic and apoptotic cells within the tumoroid structure. MTF can inhibit the integrity and proliferation of CRC tumoroids in dose-dependent manner.